(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Group Dynamics of Sempaga Daya Farmer Groups in Sembalun Bumbung Village, Sembalun District, East Lombok Regency, West Nusa Tenggara Province (NTB). The village of Sembalun Bumbung is strategically located, with significant potential in agriculture, plantation, and livestock farming. Sembalun Bumbung has the potential for crops such as rice, vegetables like lettuce, green onions, cabbage, and many others. The village is home to six Farmer Groups, including Maju Wangi, Sempaga Daya, Orong Tepas, Maju Wangi II, Tunas Makmur, and Pusuk Pujata. Based on observations, several farmer groups have been formed in Sembalun Bumbung, which have endured over time. The objective of this research is to understand the dynamics of the Sempaga Daya Farmer Group in Sembalun Bumbung Village, Sembalun District, East Lombok Regency. The research was conducted in Sembalun Bumbung Village using a survey method for data collection. The population in this study consists of all members of the Sempaga Daya Farmer Group, totaling 76 people, with a sample size of 47 people. The research method used is quantitative descriptive. The research results indicate that the dynamics of the Sempaga Daya Farmer Group are categorized as highly dynamic, with the highest score found in the "Training and Development of Farmer Groups" indicator, and the lowest score in the "Pressure" indicator. The lowest parameter for all parameters is found in the "Member satisfaction with the group" indicator within the effectiveness of the farmer group. Therefore, active participation of every member in decision-making, implementation of activities, and involvement in the planning, execution, and evaluation of the farmer group’s programs is required.